IDENTITY DISSOCIATION IN THE VIEW OF ISLAMIC PSYCHOLOGY AND THE SOLUTIONS OFFERED - Nulhakim, Lukman (TOPLAMA, 2023)
The purpose of this study is to find out the views of Islamic psychology on multiple personalities (identity dissociation) and the solutions offered to treat individuals who experience this disorder. The type of research used is qualitative research with the literature study method, in which the researcher examines various kinds of literature and draws common threads in order to get results or conclusions. While the results of this study are consistent with Islamic psychology's view of multiple personality disorder as a psychiatric disorder that has a negative impact on the individual, such as difficulties in interpersonal relationships, difficulties in decision-making, anxiety disorders, depression, and uncontrolled and unstable behaviour at work, the solutions offered by providing therapy involving spiritual, psychological, and pharmacological aspects are promising. Ruqyah therapy, psychological therapy, pharmacological therapy, spiritual therapy, and combination therapy.